Surviving the perfect storm: The role of the lender of last resort☆ - Alves, Nuno; Bonfim, Diana; Soares, Carla (Journal of Financial Intermediation, 2021)
When banks are hit by a severe liquidity shock, central banks have a key role as lenders of last resort. Despite the well-established importance of this mechanism, it is challenging to analyze it empirically. We explore a unique setting in which banks suddenly lost access to market funding due to contagion fears at the onset of the euro area sovereign debt crisis. Using monthly data at the loan, bank, and firm level, we test the role of the central bank in a scenario of imminent collapse. We find that the liquidity obtained from the central bank played a key role in temporarily supporting the supply of credit to the real economy. However, the subdued loan demand, together with moral suasion and carry trade incentives, led to an increase in banks’ sovereign bond holdings using central bank funding.